Pulmonary sclerosing hemangioma: frozen section diagnosis based on an analysis of the varied appearances in a series of thirteen cases from a single institution - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2016)
Pulmonary sclerosing hemangioma is a rare neoplasm with polymorphic histological features. The frozen section diagnosis of sclerosing hemangioma can be difficult, as it can be confused for malignancy, creating intraoperative dilemmas for pathologists. To identify the histopathologic features that may be of value in making a correct diagnosis on frozen sections, we retrospectively analyzed thirteen cases of pulmonary sclerosing hemangioma diagnosed on frozen sections in China-Japan Friendship Hospital from 2009 to 2014. We characterized the predominant patterns: solid, papillary, hemorrhagic or sclerotic. Two or more patterns were identified in twelve cases. One case exhibited only papillary pattern. A frozen section diagnosis of 'sclerosing hemangioma' was reported in ten cases, and 'benign lesion' was given in one case. Because of technical artifact and the uncommon morphology, the diagnosis was deferred in two cases. Significant cytological atypia was present in one case. Because sclerosing hemangioma is a benign tumor, accurate frozen diagnosis may avoid unnecessarily excessive surgery. Awareness of its varied patterns and distinctive cytological features, together with careful gross examination and sampling may help to avoid a diagnosis of malignancy and lead to conservative management.
Keywords: Sclerosing hemangioma; frozen section diagnosis; lung; PAPILLARY ADENOMA; LUNG; TUMOR; TTF-1